Industrialización de la riqueza vegetal: oportunidades sociales y económicas (2010)
Companies face a major challenge is this globalized economy, because to survive they have to offer new products with added value in the international market. This requires professionals trained in the methodologies for the development of new products (DNP) and university graduates must have these skills so that they can contribute to deal with this situation. A long with this they also require innovations running by the side of conservation of the environment and the taking of full advantage of available resources, either from land or technological transformation. This project is to open a window of opportunity so that the Process Engineering students can acquire the knowledge needed to perform successfully in the DNP training. A lso field employers can get valueadded products as an alternative in times of unfavourable prices.